(untitled) (Journal of Parents and Teachers, 2025)
The article begins with a true story about a child who refuses to obey his mother. In this case, the child’s negativism is an example of behaviors that young children exhibit in response to given orders. It also discusses the causes of such behaviors, how they occur, and how to respond to them.